Exclamations in English and Vietnamese – A contrastive analysis / Trần Thị Kim Tuyến; NHDKH Dr Nguyễn Thị Vân Đông - Trần, Thị Kim Tuyến
This study focuses on the syntactic and semantic features of exclamations in English and Vietnamese. Nearly 300 exclamation sentences used for analysis in this study were collected from some literary works written by Jack London and by Nam Cao. To carry out this research, the writer used descriptive, qualitative, quantitative and contrastive methods. The result of the study illustrates the fact that Vietnamese and English native speakers are similar in the choice of interjections as the most prominent element in exclamations. However, the structures of exclamations are quite different between two languages. Theoretically, with the purpose of doing the research into exclamations in English and Vietnamese literary works in terms of syntactic and semantic and raising attention from Vietnamese learners so that they can be able to use them successfully in a real world of English communication. Practically, the study provides the similarities and differences about exclamations in English and Vietnamese in terms of syntax and semantics to help Vietnamese learners of English to be aware of different ways of expressing exclamations and improve their competence and performance of English. The findings of the study is hopefully to be beneficial to those who are engaged in teaching as well as those who want to learn English as foreign language